2017
DOI: 10.1007/978-3-319-54546-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Universal Characteristics of Fractal Fluctuations in Global Mean Monthly Temperature Anomalies

Abstract: Selfsimilar space-time fractal fluctuations are generic to dynamical systems in nature such as atmospheric flows, heartbeat patterns, population dynamics, etc. The physics of the long-range correlations intrinsic to fractal fluctuations is not completely understood. It is important to quantify the physics underlying the irregular fractal fluctuations for prediction of space-time evolution of dynamical systems. A general systems theory for fractals visualising the emergence of successively larger scale fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, the current NWP ensemble forecasts are found to be typically biased and often underestimate precipitation with huge forecast ensemble uncertainty, primarily resulting from model structure and approximations of subgridscale processes [Goddard et al, 2001;Maraun et al, 2010]. Furthermore, NWP models are not very efficient in predicting heavy rainfall events [Březková et al, 2010;Hong and Lee, 2009;Khaladkar et al, 2007;Selvam, 2011]. To overcome this limitation, the mesoscale atmospheric models are used on a finer spatial resolution of 0.5-1 km incorporating land surface processes; they are effective in predicting extreme heavy rainfall events [Dodla and Ratna, 2010;Chang and Chiang, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…However, the current NWP ensemble forecasts are found to be typically biased and often underestimate precipitation with huge forecast ensemble uncertainty, primarily resulting from model structure and approximations of subgridscale processes [Goddard et al, 2001;Maraun et al, 2010]. Furthermore, NWP models are not very efficient in predicting heavy rainfall events [Březková et al, 2010;Hong and Lee, 2009;Khaladkar et al, 2007;Selvam, 2011]. To overcome this limitation, the mesoscale atmospheric models are used on a finer spatial resolution of 0.5-1 km incorporating land surface processes; they are effective in predicting extreme heavy rainfall events [Dodla and Ratna, 2010;Chang and Chiang, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Identifiable large eddies can exist in the atmosphere only for scale ratios more than 10 since, for smaller scale ratios the fractional volume dilution rate k becomes more than half. Thus atmospheric eddies of various scales, i.e., convective, meso-, synoptic and planetary scale eddies are generated by successive decadic scale range eddy mixing process starting from the basic turbulence scale (Selvam et al 1984a, b;1992;Joshi 1995 Selvam andFadnavis 1998;Joshi and Selvam 1999;Selvam 1990Selvam , 1993Selvam , 2005Selvam , 2007Selvam , 2009Selvam , 2011.…”
Section: Growth Of Macro-scale Coherent Structures From Microscopic Dmentioning
confidence: 99%
“…It would be nice if there were some general rule to the effect that, in any given complex system, the steady state which produces entropy at the maximum rate would at the same time be the steady state of maximum order and minimum entropy (Paltridge, 2009). Selvam (2011) has shown that the eddy continuum energy distribution P (Eq. 15) is the same as the Boltzmann distribution for molecular energies.…”
Section: General Systems Theory and Maximum Entropy Principle Of Clasmentioning
confidence: 99%